Effect of hand-hoe based conservation agriculture on soil fertility and maize yield in selected smallholder areas in Zimbabwe - Nyamangara, Justice; Masvaya EN; Tirivavi R; Nyengerai K (Elsevier, 2013)
Conservation agriculture (CA) based on hand-hoe prepared planting basins is being widely promoted in southern Africa, targeting resource-constrained farmers with limited access to draft power. This study was conducted across 15 districts covering four agro-ecological zones in Zimbabwe where paired CA and conventional animal drawn tillage (CADT) plots had been established on 450 farms as part of CA promotion. The aim of the study was to assess the effect of CA on soil pH, organic C, total P and maize (Zea mays L.) grain yield compared with CADT, and also to evaluate the yield benefits of mulching and crop rotation in CA with or without mineral fertilizer use. It was hypothesized that CA improved the pH, organic C, total P of the soils (Arenosols) and grain yield compared with CADT and that mulching and crop rotation in CA increased maize grain yield. A total of 1014 soil samples (0–0.2 m depth) were taken at the end of the 2009/10 cropping season and analyzed for pH, organic C and total P. Grain yield was determined in 2009/10 and 2010/11 from 0.01 ha net plots. There was no significant difference in average soil pH, total P and organic C between CA and CADT plots and therefore the hypothesis that CA improves these soil properties was rejected. Average concentration for organic C for both CA and CADT plots was less than 10 g kg−1, a minimum threshold for well managed soils. When combined with mineral fertilizer: mulching, crop rotation, and mulching + crop rotation in CA increased maize grain yield by 20–33%, 7–9% and 58–69%, respectively. With no mineral fertilizer application, mulching, crop rotation, and mulching + crop rotation depressed maize grain yield by 48%, 28% and 36%, respectively. Therefore the hypothesis that mulching and crop rotation increase maize grain yield was accepted when mineral fertilizer was added and rejected when the fertilizer was not added. It was concluded that the yield benefits of CA can only be realized when mineral fertilizer is also applied. All the three CA principles in combination with mineral fertilizer results in highest yield benefits compared with one or two principles as currently done by most smallholder farmers in Zimbabwe. Access to mineral fertilizer is an important factor in the targeting of CA promotion in smallholder areas of Zimbabwe and similar socio-ecological zones in sub-Saharan Africa.